Dynamic pricing and exchange rate pass-through: Evidence from transaction-level data - Arne J. Nagengast; Dirk Bursian; Jan-Oliver Menz (Deutsche Bundesbank, 2020)
Dynamic pricing is a widely employed pricing strategy for goods and services in which firms flexibly set prices, taking into account current market conditions. This paper studies theoretically and empirically the role of this pricing strategy in explaining the heterogeneous response of consumer prices to exchange rate fluctuations. We provide a theoretical model that illustrates how foreign producers and domestic retailers adjust prices to exchange rate fluctuations for three forms of dynamic pricing. Our model predicts that pass-through increases for clearance sales and with the capacity costs of producers in periods of high demand, while it decreases for advance purchases. We find robust empirical evidence for the model predictions using a unique German transaction-level data set of package tours at the daily frequency between 2012 and 2018 featuring rich variation of prices over time.
Keywords: F14; F31; 330; exchange rate pass-through; dynamic pricing; heterogeneity; services trade; tourism